Replacing Gas Permeable Lenses: The Benefit of a Professional in Office Dispense - Shibayama, Vivian Phan; Weissman, Barry (Canadian Journal of Optometry, 2016)
Replacing Gas Permeable Lenses: The Benefit of a Professional in Office Dispense